Mercantilist misconceptions: A détente strategy for EU-China relations - Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2012)
EU-China relations look set to grow increasingly charged in the next few years. Both sides will go through political transitions. We are on the doorstep of an era of political navel gazing that will limit their capacity to fashion a new and much needed cooperative approach towards each other. While China will go through a leadership transition, the EU increasingly moves toward new models of deeper policy integration that will require new treaty changes. Undoubtedly, these processes will take time and foster an introspective political atmosphere. Both the EU and China suffer from mercantilist misconception that guide how they look at trade and commercial policy. Even if there is a growing understanding in China that greater weight will have to given to other factors than investment and export in its growth model, its foreign economic policy remains under the spell of mercantilism. The crisis in Europe has promoted mercantilist notions and there is an increasing tendency in the European Union to use confrontational approaches to expand foreign sales. This is especially true of the EU's approach to China. Now is not a good time to reset EU-China trade and economic policy relations. What is needed now is rather a damage limitation strategy - a mechanism to contain a growing number of trade spats, some of which that could escalate into tit-for-tat protectionism.
Keywords: 330; Internationale Wirtschaftsbeziehungen; EU-Staaten; China